Oral manifestations associated with COVID-19 disease: An observational cross sectional study - Jitendra Chawla; Navaneeth Y; Satvinder Singh Bakshi; Vinoth Kumar Kalidoss; Shikha Yadav; Swapnika Polineni; Cheranjeevi Jayam (Elsevier, 2022)
Objectives: The aim of present study was to investigate oral manifestations associated with COVID-19 disease. Materials and methods: This cross-sectional study comprised 367 suspects with mild/moderate COVID-19 symptoms who reported to a tertiary care hospital's screening OPD. An in-depth case history was taken, and an oral cavity examination was performed to detect any oral findings. All participants were tested for SARS-CoV-2 using a naso-pharyngeal swab and reverse transcription polymerase chain reaction.Oral manifestations and the results of RT-PCR testing were correlated. Statistical analyses were performed using Epi Info and R software. To estimate the prevalence of oral symptoms, the Pearson chi-square test was used. Results: Oral manifestations were found in 58% of the study population. The difference in the prevalence of oral manifestations between RT-PCR positive COVID-19 patients versus RT-PCR negative suspects was statistically significant (p = 0.007) with xerostomia and dysgeusia being significantly higher in positive patients (p = 0.036 and p = 0.044 respectively) while the prevalence of stomatopyrosis and other intraoral signs was insignificant. Conclusion: Xerostomia and dysgeusia are the common oral manifestations of COVID-19.